Modifying Escherichia coli to mimic Shigella for medical microbiology laboratory teaching: a new strategy to improve biosafety in class - Zhang, Guangyuan; Liu, Jia; He, Yonglin; Du, Yuheng; Xu, Lei; Chen, Tingting; Guo, Yanan; Fu, Huichao; Li, Anlong; Tian, Yunbo; Hu, Yan; Yang, Chun; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: Laboratory teaching of medical microbiology involves highly pathogenic microorganisms, thus posing potential biosafety risks to the students and the teacher. To address these risks, non/low-pathogenic microorganisms were modified to mimic highly pathogenic ones or highly pathogenic microorganisms were attenuated directly using the CRISPR/Cas9 technology.This study describes the modification of Escherichia coli DH5α to mimic Shigella and its evaluation as a safe alternative for medical laboratory teaching.To generate E. coli DH5α △ FliC △ tnaA2a, the tnaA and FliC genes in E. coli DH5α were knocked out using CRISPR/Cas9 technology; a plasmid bearing the O-antigen determinant of S. flexneri 2a was then constructed and transformed. Acid tolerance assays and guinea pig eye tests were used to assess the viability and pathogenicity, respectively.Questionnaires were used to analyse teaching effectiveness and the opinions of teachers and students.The survey revealed that most teachers and students were inclined towards real-time laboratory classes than virtual classes or observation of plastic specimens. However, many students did not abide by the safety regulations, and most encountered potential biosafety hazards in the laboratory. E. coli DH5α△FliC△tnaA2a was biochemically and antigenically analogous to S. flexneri 2a and had lower resistance to acid than E. coli. There was no toxicity observed in guinea pigs. Most of teachers and students were unable to distinguish E. coli DH5α△ FliC△tnaA2a from pure S. flexneri 2a in class. Students who used E. coli DH5α△FliC△tnaA2a in their practice had similar performance in simulated examinations compared to students who used real S. flexneri 2a, but significantly higher than the virtual experimental group.Discussion: This approach can be applied to other high-risk pathogenic microorganisms to reduce the potential biosafety risks in medical laboratory-based teaching and provide a new strategy for the development of experimental materials.